Modulating Inflammation-Mediated Diseases via Natural Phenolic Compounds Loaded in Nanocarrier Systems - Tojofaniry Fabien Rakotondrabe; Min-Xia Fan; Felix Wambua Muema; Ming-Quan Guo (MDPI AG, 2023)
The global increase and prevalence of inflammatory-mediated diseases have been a great menace to human welfare. Several works have demonstrated the anti-inflammatory potentials of natural polyphenolic compounds, including flavonoid derivatives (EGCG, rutin, apigenin, naringenin) and phenolic acids (GA, CA, etc.), among others (resveratrol, curcumin, etc.). In order to improve the stability and bioavailability of these natural polyphenolic compounds, their recent loading applications in both organic (liposomes, micelles, dendrimers, etc.) and inorganic (mesoporous silica, heavy metals, etc.) nanocarrier technologies are being employed. A great number of studies have highlighted that, apart from improving their stability and bioavailability, nanocarrier systems also enhance their target delivery, while reducing drug toxicity and adverse effects. This review article, therefore, covers the recent advances in the drug delivery of anti-inflammatory agents loaded with natural polyphenolics by the application of both organic and inorganic nanocarriers. Even though nanocarrier technology offers a variety of possible anti-inflammatory advantages to naturally occurring polyphenols, the complexes' inherent properties and mechanisms of action have not yet been fully investigated. Thus, expanding the quest on novel natural polyphenolic-loaded delivery systems, together with the optimization of complexes' activity toward inflammation, will be a new direction of future efforts.